Co-infection of SARS-CoV-2 with other respiratory viruses and performance of lower respiratory tract samples for the diagnosis of COVID-19. (January 2021) - Burrel, Sonia; Hausfater, Pierre; Dres, Martin; Pourcher, Valérie; Luyt, Charles-Edouard; Teyssou, Elisa; Soulié, Cathia; Calvez, Vincent; Marcelin, Anne-Geneviève; Boutolleau, David
Highlights: The extent of co-infections of SARS-CoV-2 with other respiratory viruses remains unknown. Lower respiratory tract samples improved the diagnosis of non-SARS-CoV-2 respiratory infections. 7% of SARS-CoV-2-positive patients were co-infected with other respiratory viruses. The detection of other respiratory viruses could not rule out SARS-CoV-2 co-infection. Lower respiratory tract samples increased the accuracy of diagnosis of COVID-19. Abstract: Objectives: This study was performed during the early outbreak period of coronavirus disease 2019 (COVID-19) and the seasonal epidemics of other respiratory viral infections, in order to describe the extent of co-infections of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with other respiratory viruses. It also compared the diagnostic performances of upper respiratory tract (URT) and lower respiratory tract (LRT) samples for SARS-CoV-2 infection. Methods: From 25 January to 29 March 2020, all URT and LRT samples collected from patients with suspected COVID-19 received in the virology laboratory of Pitié-Salpêtrière University Hospital (Paris, France) were simultaneously tested for SARS-CoV-2 and other respiratory viruses. Results: A total of 1423 consecutive patients were tested: 677 (47.6%) males, 746 (52.4%) females, median age 50 (range, 1–103) years. Twenty-one (1.5%) patients were positive for both SARS-CoV-2 and other respiratory viruses. The detection rate of SARS-CoV-2 was significantly higher in LRT than in URT (53.6% vs. 13.4%; p < 0.0001). The analysis of paired samples from 117 (8.2%) patients showed that SARS-CoV-2 load was lower in URT than in LRT samples in 65% of cases. Conclusion: The detection of other respiratory viruses in patients during this epidemic period could not rule out SARS-CoV-2 co-infection. Furthermore, LRT samples increased the accuracy of diagnosis of COVID-19.